The response of Hawaiian native weed Eragrostis variabilis and some crop plants to germination substrate acidity = Tanggapan Eragristis variabilis (rumput Hawaii dan beberapa tanaman pertanian terhadap keasaman ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The principal source of the acid rain around volcanoes is SO2 which undergoes oxidation in the atmosphere forming H2SO4 aerosol. In Kilauea volcano, Hawaii, recent Held measureÂ¬ments show that sulfate content alone can not account for acidity below pH 4.0. It has been suggested that biogenic formate and other organic acids may account for the extra acidity. The significane of anions SO4, NO3, Cl, and formate are tested in the germination process of the seeds of native Hawaiian Eragrostis variabilis, and commercial Phaseolus aureus, Zea mays, up land and lowland rice (Oriza sativa). Deionized water with phosphate buffer at pH 7.0 was used as a control medium, and H2SO4, or HCL, or HNO3, or formic acid was added in each treatment to reach desired pH value. Germination inhibition was observed at pH 2.5 and 2.0, whole stimulation was observed at pH 3.0 and 3.5 in all species used. Formic and sulfate anions inhibit germination more than the other anions. There is tendency for species variation in the response to acidity among those used. The responses of an Hawaiian species andemic in the vicinity of an active volcano were only better than responses of some commercial species at pH 2.5 with formic anion and at pH 3.5 with nitrate anion.